2012
DOI: 10.3892/or.2012.2040
|View full text |Cite
|
Sign up to set email alerts
|

Significance of stromal decorin expression during the progression of breast cancer

Abstract: Abstract. Decorin, a small leucine-rich proteoglycan and important component of the extracellular matrix (ECM), is a natural anticancer agent that modulates several receptors involved in cell growth and survival. Reductions in decorin expression may weaken the ECM and enhance the effectiveness of these receptors and may, consequently, lead to tumor spreading. To determine the contribution of stromal decorin regulation in the development of breast cancer and in tumor invasiveness, immunohistochemistry was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
(22 reference statements)
6
26
0
Order By: Relevance
“…On the contrary to the report published by El Behi et al 41 that states overexpression of Decorin in muscle invasive bladder cancer, we observed a reduced protein expression of Decorin by IHC and western blotting in tumour tissue as compared with adjacent non-tumour tissue. Previously, Sainio et al 42 had shown a similar low stromal Decorin expression in areas rich in bladder cancer cells as compared with non-malignant bladder tissue, and Oda et al 43 had observed a reduced immunostaining in stroma of invasive cancer and in situ breast cancer as compared with normal breast tissue. Thus, our findings in bladder cancer for the expression of Decorin are in accordance with the previous studies done in prostate, breast, and oesophageal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary to the report published by El Behi et al 41 that states overexpression of Decorin in muscle invasive bladder cancer, we observed a reduced protein expression of Decorin by IHC and western blotting in tumour tissue as compared with adjacent non-tumour tissue. Previously, Sainio et al 42 had shown a similar low stromal Decorin expression in areas rich in bladder cancer cells as compared with non-malignant bladder tissue, and Oda et al 43 had observed a reduced immunostaining in stroma of invasive cancer and in situ breast cancer as compared with normal breast tissue. Thus, our findings in bladder cancer for the expression of Decorin are in accordance with the previous studies done in prostate, breast, and oesophageal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…15 BC lumican was highly abundant relative to decorin, while biglycan and fibromodulin are only detected occasionally [143] lumican mRNA was increased in tumors while decorin mRNA was decreased in neoplastic relative to adjacent normal stroma along with an increase in lumican, but not decorin IHC for decorin 98 samples IBC and 22 were from patients with DCIS Decorin was observed in stroma but not epithelia. Average decorin expression decreased from normal to DCIS to IDC [48] IHC for Syndecan 1,4, and Glypican 1 207 BC Glypican-1 detected in a small sample of BC [144] Higher level of Syndecan 1 and -4 predicted higher…”
Section: Altered Ecm and Altered Cell Responsementioning
confidence: 98%
“…Importantly, gene expression patterns of normal stroma adjacent to breast cancers shows a different gene expression pattern from normal tissue from unaffected patients [46]. Changes in stromal ECM are observed even in ductal carcinoma in situ (DCIS), where carcinoma cells are confined within an intact basement membrane, including increased deposition of versican [47], loss of decorin [48], and altered expression of Col11A1 [46,49].…”
Section: Stromamentioning
confidence: 99%
“…Decorin is also found in tumor ECM and is mainly attributed to surrounding, non-malignant stromal cells (tumor cells express little decorin) [1517]. However, decorin expression is decreased in stromal cells of many tumors compared to normal tissues and inversely correlates with prognosis of breast and lung carcinomas [16, 18, 19]. Declined decorin in the bone marrow matrix is also associated with the clinical progression of multiple myeloma [20].…”
Section: Small Leucine-rich Proteoglycans (Slrps)mentioning
confidence: 99%
“…Declined decorin in the bone marrow matrix is also associated with the clinical progression of multiple myeloma [20]. Interestingly, decorin acts as a tumor suppressor in a number of cancers, including breast, prostate, ovarian and colon [16, 21–23]. This function is partially due to the ability of decorin to bind to and inhibit function of RTKs such as epidermal growth factor receptor (EGFR), insulin-like growth factor receptor I (IGF-IR) and hepatocyte growth factor receptor (c-Met) [2426].…”
Section: Small Leucine-rich Proteoglycans (Slrps)mentioning
confidence: 99%